The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1021/acs.chemmater.5b03417
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Heating-Up Synthesis of Monodisperse Cu2ZnSnS4 Nanocrystals

Abstract: Monodisperse Cu2ZnSnS4 (CZTS) nanocrystals were prepared by a facile, high yield, scalable and high concentration heating-up procedure. An efficient mixing and heat transfer in the reaction mixture using intensive argon bubbling and a careful control of the heating ramp stability were key parameters to minimize the nanocrystal size distribution. Optimized synthesis conditions allowed the production of several grams of highly monodisperse CZTS nanocrystals per batch, with a 5wt% concentration and a yield above … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 35 publications
1
41
0
Order By: Relevance
“…57 However, it was repeatedly reported that Cu-based NCs typically have tightly bound amines bound to the surface. 13,58 It should however be noted that OLA is quite easily desorbed during purification suggesting only a moderate binding affinity for the NC surface, in line with L-type ligand behaviour. To facilitate charge transport/transfer, CASe NCs were thoroughly purified by multiple precipitation/re-dispersion steps and subsequently treated with NH 4 SCN, which could efficiently displace remaining OLA.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…57 However, it was repeatedly reported that Cu-based NCs typically have tightly bound amines bound to the surface. 13,58 It should however be noted that OLA is quite easily desorbed during purification suggesting only a moderate binding affinity for the NC surface, in line with L-type ligand behaviour. To facilitate charge transport/transfer, CASe NCs were thoroughly purified by multiple precipitation/re-dispersion steps and subsequently treated with NH 4 SCN, which could efficiently displace remaining OLA.…”
Section: Resultsmentioning
confidence: 88%
“…[1][2][3][4][5][6][7] Beyond the best studied ternary and quaternary Cu-Ga-In, [8][9][10] Cu-Zn-Sn, [11][12][13][14][15] Cu-Zn-Ge 16,17 compounds, some I−V−VI tetrahedrally coordinated semiconductors also offer excellent functional properties, but remain largely underexplored. In particular, Cu 3 SbSe 4 (CASe) is a semiconductor with a relatively small direct band gap of 0.3 eV and a defect-related carrier density on the order of 10 18 cm -3 at ambient temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The spectra has been deconvoluted to gain a better understanding of the different phases present in the material and changes in their relative intensity with changes in the precursor ratio. The peaks at ~334 cm -1 and ~287 cm -1 are the primary and secondary characteristic peaks for kesterite CZTS phase respectively [32][33][34]. The peaks at ~358 cm -1 and ~657 cm -1 can be attributed to ZnS [33,35] while the peak at ~471 cm -1 belongs to Cu2-xS [33], both of which are unwanted secondary phases.…”
Section: Sulfur Variation (Samples S1-s3)mentioning
confidence: 95%
“…The peaks at ~334 cm -1 and ~287 cm -1 are the primary and secondary characteristic peaks for kesterite CZTS phase respectively [32][33][34]. The peaks at ~358 cm -1 and ~657 cm -1 can be attributed to ZnS [33,35] while the peak at ~471 cm -1 belongs to Cu2-xS [33], both of which are unwanted secondary phases. As the quantity of the sulfur precursor is increased, the intensity of the peaks indicating kesterite CZTS phase increase while those for the secondary phases of ZnS and Cu2-xS decrease.…”
Section: Sulfur Variation (Samples S1-s3)mentioning
confidence: 95%
“…From this we expected to obtain insights into the interplay of nanoparticle surface curvature and block copolymer interfacial curvature on the self-assembled morphology.W ec hose poly(styrene-b-isoprene) (PS-PI) block copolymers because their phase behavior has been wellestablished. [19] Theb lock copolymer molecular weights,c ompositions as well as the diameters of the nanoparticles are given in Table 1. PEHA shows strong coordinative binding,but still possesses sufficient surface mobility to reach high grafting densities.…”
mentioning
confidence: 99%